Case Report: Masson’s Tumor in Maxillary Sinus with Concurrent Inferior Turbinate Hemangioma, a Rare Entity - Manpreet Kaur Kuldep Singh; Revadi Govindaraju (Talenta Publisher, 2025)
Background: Masson's tumour, also known as intravascular papillary endothelial hyperplasia (IPEH), is a relatively uncommon benign vascular lesion that develops in organising thrombus, whereas hemangiomas are benign vascular tumours that can develop anywhere there are blood vessels. Objective: To report a rare case of Masson's tumour in the maxillary sinus with concurrent inferior turbinate hemangioma and to explore the possible association between these two vascular anomalies. Methods: A 31-year-old female patient who is otherwise healthy presented with intermittent epistaxis, facial pain, and numbness. Imaging examinations discovered a mass in the maxillary sinus, which led to a possible malignancy diagnosis. Results: A post-surgery histological report supported the diagnosis of a benign vascular lesion called Masson's tumour in the maxillary sinus with concurrent inferior turbinate hemangioma. Based on our literature review, this is the 12th case of IPEH in the maxillary sinus. Conclusion: The concurrent presentation of Masson's tumour in the maxillary sinus with an inferior turbinate hemangioma suggests a possible association between these two vascular anomalies.